2017
DOI: 10.1186/s13287-017-0660-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes of human placenta-derived mesenchymal stem cells stimulate angiogenesis

Abstract: BackgroundThe therapeutic potential of mesenchymal stem cells (MSCs) may be attributed partly to humoral factors such as growth factors, cytokines, and chemokines. Human term placental tissue-derived MSCs (PlaMSCs), or conditioned medium left over from cultures of these cells, have been reported to enhance angiogenesis. Recently, the exosome, which can transport a diverse suite of macromolecules, has gained attention as a novel intercellular communication tool. However, the potential role of the exosome in Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 31 publications
8
131
0
1
Order By: Relevance
“…Komaki et al and Nakamura et al showed an equal induction of endothelial tube formation by CM and EVs derived from MSCs of human placental tissue and bone marrow. The associated EV-depleted CM did not affect this angiogenic step [24,62]. Similar results were also observed for human adipose-derived MSCs [63] and rat BM-MSCs [64].…”
Section: Discussionsupporting
confidence: 75%
“…Komaki et al and Nakamura et al showed an equal induction of endothelial tube formation by CM and EVs derived from MSCs of human placental tissue and bone marrow. The associated EV-depleted CM did not affect this angiogenic step [24,62]. Similar results were also observed for human adipose-derived MSCs [63] and rat BM-MSCs [64].…”
Section: Discussionsupporting
confidence: 75%
“…Likewise, EVs from UC-MSCs overexpressing the tissue matrix metalloproteinase inhibitor 2 (TIMP2) or the cardioprotective stromal-derived factor 1 alpha (SFD1a) have been shown to limit detrimental ventricular remodelling via the pro-survival Akt/Sfrp2 pathway and to inhibit apoptosis and autophagy of myocardial cells while sustaining local angiogenesis in preclinical rodent models of MI [200,201]. MSCs derived from human term placenta, also referred to as amniotic mesenchymal stromal cells (AMSCs), are well-known for their (immuno)modulatory properties [202,203]; EVs released by human term placenta-MSCs have been recently demonstrated exertion of relevant therapeutic effects as supporting new vessel development in vitro and in vivo [204], with nitric oxide (NO)-releasing polymer stimulation as a functional trigger of exosomal enrichment of pro-angiogenic VEGF and miR-126 [205]. Notably, placenta-MSCs and their derived EVs have been shown to counteract skewing of myoblasts to fibrogenic phenotype and collagen IV expression in the cardiac tissue of preclinical models of Duchenne musclar dystrophy, via targeted delivery of miR-29c [206].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…To observe interactions between MSCs-exo and HUVECs, laser scanning confocal microscopy was used here. For uorescence staining of exosomes, MSCs-exo (8×10 9 ), miRNA-21-5p-KD-exo (8×10 9 ), and miRNA-21-5p-OE-exo (8×10 9 ) were respectively incubated with green uorescent dye PKH67 (MINI67-1KT, SIGMA) for 5 min at room temperature, followed by twice PBS wash using ultracentrifugation, as described previously 10 . Then, human umbilical vein endothelial cells (HUVECs) were co-cultured with either PBS (control), MSCs-exo, miRNA-21-5p-KD-exo or miRNA-21-5p-OE-exo for 4 hours at 37°C with 5% CO2.…”
Section: Confocal Imagingmentioning
confidence: 99%
“…Recent studies have reported that MSCs secrete exosomes, [9] which are membranous vesicles with diameter of 30-150 nm and density of 1.10 ~ 1.18 g/ml. [10] Exosomes contain various molecules including proteins, mRNA, and microRNA (miRNA), and these molecules can regulate the gene network of target cells as novel intercellular communicators. [11][12][13] During the past a few years, exosomes and exosome miRNA of MSCs in the angiogenesis had been increasingly attracted researcher's interests.…”
Section: Introductionmentioning
confidence: 99%